Full scale investigation of GCL damage mechanisms in small earth dam retrofit applications under earthquake loading. Issue 4 (August 2019) - Sawada, Yutaka; Nakazawa, Hiroshi; Take, W. Andy; Kawabata, Toshinori
Abstract: This paper reports results of full scale testing to further explore potential GCL damage mechanisms in earth dam retrofit applications in seismically active areas; in particular, to a) investigate whether shear displacements could reduce the magnitude of GCL panel overlap during earthquake shaking; b) explore the influence of gravel particles on GCL thickness at localised point of contact; and c) observe the consequences of an accidental exposure of an uncovered GCL to short duration rainfall in terms of moisture content and effects during subsequent compaction. The results of these experiments indicate that even under severe shaking no movements were detected at the GCL panel overlap. Whereas gravel particles were observed to locally reduce the thickness of the GCL to 2.2 mm, no plowing of the particle into the GCL occurred due to a lack of shear displacement at the interface, resulting in no localised internal erosion through the barrier. Furthermore, hydration of GCL panels during construction due to surface wetting was observed to result in a state of hydration less than its post-construction state. These results indicate that although each of the three GCL damage mechanisms cannot be ruled out to ever be relevant in practice, the performance of the GCL retrofitted earth dam tested was satisfactory under even severe Level 2 earthquake shaking, and suggests that the retrofitting of small earth dams with GCLs is a promising strategy to improve their static and seismic resistance.